VD_FINDINFO HC / 2010 / 99 vom 28. Januar 2010 - VD Tribunal cantonal (2010)
BAIL À LOYER, LOYER, RÉDUCTIONEN GÉNÉRAL, RESTITUTIONEN GÉNÉRAL, DÉFAUT DE LA CHOSE, PRESCRIPTION | 127 CO, 128 ch. 1 CO, 128 CO, 256 al. 1 CO, 256 CO, 259 CO, 259a al. 1 CO, 259a al. 1 let. a CO, 259a al. 1 let. b CO, 259a CO, 259d CO, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 13 LTB